Polarizing triangular cyclic interferometer for characterizing optical samples with birefringent properties - R. Kaewon (2018)
© 2015 SPIE. This paper presents the polarizing triangular cyclic interferometer (pTCi) for characterizing optical samples with birefringent properties such as half- and quarter-wave plates. The interferometric system was set up to analyze the phase retardation of wave retarders in both qualitative and quantitative aspects. For the qualitative aspect, the distinct signal outputs from the inspected birefringent components oriented at particular angles are employed to distinguish different types of optical devices. For the quantitative aspect, the same arrangement could determine the phase difference γ of unknown retarders, so that it could be used to characterize types of samples. The experimental results showed the corresponding results obtained from both mentioned aspects where γ were measured to be 89.62° and 177.17° for half- and quarter-wave plates, respectively. The pTCi has been proved to be a proper scheme to characterize optical samples with birefringent properties.